2005
DOI: 10.1111/j.1439-0426.2005.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile white sturgeon (Acipenser transmontanus) habitat and distribution in the Lower Fraser River, downstream of Hope, BC, Canada

Abstract: The primary objective of this study was to identify and characterize juvenile white sturgeon (Acipenser transmontanus) habitat in the Lower Fraser River downstream of Hope, BC, Canada. A secondary objective was to estimate the juvenile white sturgeon population in the Lower Fraser River. A total of 1867 white sturgeon was captured with gill nets at 26 sites in the Lower Fraser River. The greatest numbers of sturgeon were caught in three sloughs; all but three sturgeon were captured in the June to August period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Less is known about habitat use of feeding larvae and early juveniles. However, in the Fraser River, juveniles use lower velocity areas such as side channels, sloughs, and deeper areas of the mainstem (Bennett et al., ; Glova et al., ). The decreased availability of such habitats has been identified as a potential threat to juvenile survival (Nelson et al., ).…”
Section: Habitat Usementioning
confidence: 99%
“…Less is known about habitat use of feeding larvae and early juveniles. However, in the Fraser River, juveniles use lower velocity areas such as side channels, sloughs, and deeper areas of the mainstem (Bennett et al., ; Glova et al., ). The decreased availability of such habitats has been identified as a potential threat to juvenile survival (Nelson et al., ).…”
Section: Habitat Usementioning
confidence: 99%
“…In a previous study, we found juvenile significantly preferred sand substrate when given a choice of four substrates (numbers indicate particle diameter): sand (<0.02 cm), small gravel (1.0 -2.0 cm), medium gravel (4.0 -5.0 cm), and rubble (13.0 -15.0 cm) [16]. There are several papers that also show a preference for sand substrate by juvenile or adult sturgeons, including A. fulvescens [7] [9]; A. transmontanus [8]; A. gueldenstaedtii; A. brevirostrum [10]; and Scaphirhynchus albus [16]. Peake tested juvenile A. fulvescens preference for sand, gravel, rock or smooth plastic bottom and found a strong preference for sand [7].…”
Section: Discussionmentioning
confidence: 87%
“…White sturgeon is the largest freshwater fish in North America. Adults occupy a range of deepwater mainstem habitats in large rivers; habitat use by young juveniles can include low-velocity habitats such as side channels, tributary confluences, backwaters and sloughs (Bennett et al 2005) or deep, low-velocity mainstem habitats and lake habitat (RL&L Environmental Services Ltd. 2000;Neufeld and Spence 2002;Golder Associates Ltd. 2003). Although riparian vegetation and large wood of riparian origin may have considerable influence on the channel and floodplain structure of medium to large rivers (Latterell et al 2006;Latterell and Naiman 2007;Naiman et al 2010), at present, there is no clear evidence that modification of the riparian zone will degrade in-stream critical habitat attributes for the listed populations of white sturgeon or decrease their probability of persistence (Table 1); consequently, recovery teams in the USA and Canada did not identify riparian habitat as biologically critical (US Fish and Wildlife Service 1999; National Recovery Team for White Sturgeon 2009).…”
Section: Does Riparian Habitat Meet Biological Criteria For Critical mentioning
confidence: 99%